OBE (Outcome-Based Education) Framework Politeknik Negeri Tanah Laut - Herpendi; Zulfahri, Aidil Fajar; Hafizd, Khairul Anwar; Nurependi (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2025)
In 2025, Politeknik Negeri Tanah Laut (POLITALA) will enter its 16th year with various prestigious achievements, one of which was receiving the best SAKIP award among all polytechnics in Indonesia in 2021. This accomplishment cannot be separated from the institution’s strong management and POLITALA’s efforts to adapt to digital developments in order to realize its vision of becoming a leading polytechnic with national competitiveness. Several initiatives have been implemented, such as the adoption of SIPADU as the academic information system for students and the application of an Outcome-Based Education (OBE) curriculum, which emphasizes the achievement of specific and measurable learning outcomes. However, the diversity of study programs and academic backgrounds of lecturers at POLITALA often leads to differences in interpreting academic guidelines. Therefore, a structured system is needed as a guide for curriculum development in each study program. This research aims to develop an information system for OBE-based curriculum design in a systematic manner, starting from the determination of Graduate Profiles (PL) to mapping the contribution of each course in supporting the achievement of those profiles.